Ketahanan Pangan Di Kabupaten Jombang 2018-2021 - Mudjib Mustain; Humiadah Muafiqie; Trusti Diani Henartiwi (Journal of Public Power, 2022)
The purpose of this study was to determine the level of consumption and food needs in Jombang Regency. This research is included in the type of descriptive research with secondary data, as a source of data obtained from the Office of Food Security, Logistics Business Entity and various parties directly related to food security in Jombang Regency. The research was carried out correctly, objectively, and accurately with interviews, field research, questionnaires and documentation. The sample uses a time series, namely data from the last 4 (five) years from the level of consumption and food needs in Jombang Regency and analyzed using qualitative descriptive data analysis techniques. The result is that the energy consumption of the people of Jombang Regency is 1,631.0 kcal/capita/day, not meeting the ideal energy consumption (2,000 kcal/capita/day). Consumption of protein at the district level is 46.1 grams/capita/day, it does not meet the ideal protein consumption (52 grams/capita/day). People still depend on rice as a staple, as seen in the consumption of grain 250.6 grams/capita/day, consumption of grains is dominated by rice consumption of 235.4 grams/capita/day, corn 2.0 grams/capita/day and wheat flour 13.2 grams/capita/day. Food consumption in the people of Jombang is less diverse, as can be seen in the Hope Food Pattern (PPH) Score in Jombang Regency of 79.2, the target PPH score in 2015 is 95. The strategy of the Regional Government in efforts to develop food security in Indonesia Jombang Regency is to increase the socialization of the P2KP program to the community in collaboration with PKK and related agencies, so that people understand the diversification and quality of food consumption. the creation of food security as a vehicle, guaranteeing the availability of food at affordable prices and promising to encourage increased production. Fulfillment of sufficient food, both in quantity and quality, safe, equitable and affordable by all households is the main target in economic development. The increasing demand for food in line with population growth encourages the acceleration of food production in order to realize price stabilization and food availability, so that food security is closely related to the government's ability to maintain the stabilization of food supply and the carrying capacity of the agricultural sector.